The Physicochemical and Microbiological Qualities of Pegagan Duck Meat Preserved with Different Concentrations of Liquid Smoke and Storage Period - Fitra Yosi; Dyah Wahyuni; Meisji Liana Sari; Sofia Sandi (Buletin Peternakan, 2018)
The aim of this research was to investigate the quality of physicochemistry and microbiology of Pegagan duck meat preserved with various concentrations of liquid smoke and storage time. This study used a complete randomized design (CRD) with a 4x2 factorial pattern. The first factor was the concentration of liquid smoke solution consisted of 4 levels, namely 2; 4; 6, and 8% (v/v). The second factor was the storage time which includes 2 levels ie 12 and 24 hours. The replication used was 4 times. The observed variables were physical quality of meat (water holding capacity, cooking loss, and tenderness), chemical quality (moisture content, protein content, and fat content), and microbiological quality (total microbes, pH, acid total, and total phenol). The data were processed by analysis of variance, followed by Duncan's multiple range test (DMRT). The results showed that there was a significant interaction (P<0.05) between liquid smoke concentration and storage time to water holding capacity, cooking loss, tenderness, fat content, total phenol, total microbial, total acid, and pH in Pegagan duck meat but did not show a significant interaction with other variables. It could be concluded that the optimum liquid smoke concentration was 4% and the optimal storage time was 12 hours.